Supply of Consumer Goods, Per Capita Consumption due to Covid-19 Pandemic - I Wayan Widnyana; Sapta Rini Widyawati (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
The Covid-19 pandemic that is happening now is affecting the economy. This study aims to examine changes in the supply of consumer goods to Bali from outside Bali in the Indonesian territory and changes in the per capita consumption of the Balinese population, due to the Covid-19 pandemic. Two events were observed, namely the first event was the announcement of the first positive case of Covid-19 in Indonesia, and the 2nd event was the determination of the status of a national disaster by the Indonesian government. Data analysis was performed using a different test with the SPSS v.23 program. The results of the analysis found that there was a difference in the supply of consumer goods to Bali from outside Bali and the per capita consumption of the Balinese population in the first and 2nd events. The supply of consumer goods and per capita consumption decreased significantly after the announcement of the first positive case of Covid-19 and then further decreased after the Indonesian government declared a national disaster status. The determination of the status of a national disaster has a greater impact on reducing the per capita consumption of the Balinese population than the announcement of the first Covid-19 patient. As a result of Covid-19, it is hoped that the Bali Provincial Government needs to make policy breakthroughs to encourage the fulfillment of consumer goods needs in Bali independently so that they do not always depend on supplies from outside Bali. The Covid-19 pandemic has reduced people's income and reduced buying power, thus demanding people to be smarter in managing finances, including adjusting consumption patterns according to the priority scale of needs.